STUDI PERBANDINGAN SEJARAH DIPLOMASI ISLAM DAN BARAT - Imam Taufik Alkhotob (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
The study of the history of diplomacy between the West and Islam is interesting to compare. Considering that the theory and science of relations between countries currently rely a lot on these two great civilizations; Islam and the West. Each influence each other and sometimes cannot be reconciled. The character of the West is more inclined to make diplomacy a tool to achieve the goals of the State by means of trickery and intrigue. So it seems very negative. Meanwhile, in the history of Islam as put by the Prophet Muhammad sallallhu 'alaihi wasallam, it is far from that bad stigma. Therefore, the conclusions of this paper are; Islam offers the power of diplomacy on the basis of equality between races, tribes and nations. Safeguard the lives, property and honor of diplomats. Keep safe between the strong and the weak. Keeping the diplomacy process away from fraud, trickery and violence. All of this shows that the Islamic conception of relations between States, between power in one area and another, is running in a modern and civilized manner.